The influence of oxygen content on the Tc of HTS Hg-1245 - Itskevich, E.S. (Физика низких температур, 1999)
It is shown that low temperature asymptotics of various thermodynamic and transport properties of s-wave superconductors can become power-law ones if wide distributions of gap values exist, originating from structure domains, charge stripes, charge-density waves or other mesoscopic nonhomogeneities. The relevant experimental data for high-Tc oxides are analyzed on the basis of the developed theory.